Penilaian Kinerja Badan Penyelesaian Sengketa Konsumen (BPSK) Berdasarkan Putusan Mahkamah Agung Nomor 175K/Pdt.Sus-BPSK/2021 - Jessica Jessica; Ariawan Gunadi (UNES Law Review, 2023)
The Consumer Dispute Settlement Agency (BPSK) is a semi-court institution that has the authority to resolve and decide disputes between consumers and business actors on a non-litigation basis. Law Number 8 of 1999 concerning Consumer Protection or commonly known as UUPK is a regulatory basis used by BPSK in deciding consumer disputes because UUPK is a law that overshadows all laws that intend to provide protection to consumers. In practice, BPSK is often referred to as an institution that has the authority to examine, resolve, and decide a dispute with a final and binding decision. However, in one example of a case in the Supreme Court decision Number 175K / Pdt.Sus-BPSK / 2021, BPSK decided to impose sanctions on perpetrators outside the authority of BPSK. This is a problem of how to assess the performance of BPSK in deciding consumer disputes. The research method used is normative juridical with a case approach. To improve the performance of BPSK in deciding consumer disputes, it is necessary to update the contradictory UUPK regulations so that BPSK decisions do not cause legal uncertainty for protected consumers. The role burden borne by BPSK is also not balanced with existing Human Resources, so it needs to be improved so that BPSK's performance in deciding consumer disputes can be more careful without overriding applicable laws.